2008
DOI: 10.1021/jp801300j
|View full text |Cite
|
Sign up to set email alerts
|

TiO2Nanotube Arrays Annealed in N2for Efficient Lithium-Ion Intercalation

Abstract: Anatase titania nanotube arrays were fabricated by means of anodization and annealed at 300, 400, and 500°C in N 2 . Lithium-ion intercalation measurements revealed that annealing in nitrogen resulted in much enhanced lithium-ion insertion capacity and improved cyclic stability. TiO 2 nanotube arrays annealed at 300°C exhibited the best lithium-ion intercalation property with an initial high discharge capacity up to 240 mA · h/g at a high current density of 320 mA/g. The excellent discharge capacity at a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…Similarly, the cyclic and rate performance Ar-annealed were close to Air-annealed TNAs, but its specific capacity is the lowest. The specific capacity and rate performance of N 2 annealed sample were better than Ar-annealed, which attributed to the reduction of charge transfer resistance of N 2 annealed atmosphere while cyclic performance is similar to Ar-annealed TNAs [40]. So the comparative study on the electrochemical properties of TNAs annealed in different atmosphere revealed that enhancement of specific capacity might be obtained.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, the cyclic and rate performance Ar-annealed were close to Air-annealed TNAs, but its specific capacity is the lowest. The specific capacity and rate performance of N 2 annealed sample were better than Ar-annealed, which attributed to the reduction of charge transfer resistance of N 2 annealed atmosphere while cyclic performance is similar to Ar-annealed TNAs [40]. So the comparative study on the electrochemical properties of TNAs annealed in different atmosphere revealed that enhancement of specific capacity might be obtained.…”
Section: Resultsmentioning
confidence: 89%
“…However, the areal specific capacity, even for the optimized TNAs, is found to be low (Tauseef Anwar et al 2015). Three different methods have been proposed to enhance the specific capacity: (1) doping TNAs with metal or nonmetal elements (Kyeremateng et al 2013b;Liu et al 2008Liu et al , 2009); (2) coating TNAs with conductive reagents (Guan and Wang 2013;Kim et al 2010;Zhang et al 2009); (3) modify TNAs with oxide materials that have larger capacities [SnO 2 (Meng et al 2013), Co 3 O 4 (Fan et al 2013;Kyeremateng et al 2013a), Nb 2 O 5 (Yang et al 2013) and Fe 2 O 3 (Yu et al 2013)] to yield hybrid or composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, TNAs have lower areal specific capacity (Anwar et al 2015) which can be improved by adopting different strategies such as, metal or non-metal element doping (Liu et al 2008(Liu et al , 2014, annealing in different atmosphere (Lu et al 2012), conductive coating , and by compositing with the higher capacity materials . Molybdenum disulfide (MoS 2 ) is an attractive material for the practical applications including hydrogen storage, (Chen et al 2001;Ye et al 2006) as catalysts, (Hinnemann et al 2005;Lukowski et al 2013) lubricants, (Chhowalla and Amaratunga 2000;Savan et al 2000) double-layer capacitor (Cao et al 2013;Soon and Loh 2007) as well as lithiun-ion batteries (Hwang et al 2011;Stephenson et al 2014;Feng et al 2009;Li et al 2009;Dominko et al 2002).…”
Section: Introductionmentioning
confidence: 99%